Genomic and epigenomic alterations in prostate cancer - Aschelter, Anna Maria; Giacinti, Silvana; Caporello, Paola; Marchetti, Paolo (Frontiers in Endocrinology, 2012)
Prostate cancer (PC) is the second most frequently diagnosed cancer and the second leading cause of cancer deaths in man. The treatment of localized PC includes surgery or radiation therapy. In case of relapse after a definitive treatment or in patients with locally advanced or metastatic disease, the standard treatment includes the androgen-deprivation therapy (ADT). By reducing the levels of Testosterone and dihydrotestosterone (DHT) under the castration threshold, the ADT acts on the androgen receptor (AR), even if indirectly. The effects of the ADT are usually temporary and nearly all patients, initially sensitive to the androgen ablation therapy, have a disease progression after a 18-24 months medium term. This is probably due to the selection of the cancer cell clones and to their acquisition of critical somatic genome and epigenomic changes. This review aims to provide an overview about the genetic and epigenetic alterations having a crucial role in the carcinogenesis and in the disease progression toward the castration resistant prostate cancer (CRPC). We focused on the role of the androgen receptor, on its signaling cascade and on the clinical implications that the knowledge of these aspects would have on hormonal therapy, on its failure and its toxicity.